Roman Comedy - Konstan, David (Book collections on Project MUSE., 1983)
This book explores the social institutions, the prevailing social values, and the ideology of the ancient city-state as revealed in Roman Comedy. "The very essence of comedy is social," writes David Konstan, "and in the complex movement of its plots we may be able to discern the lineaments and contradictions of the reigning ideas of an age."David Konstan looks closely at eight plays: Plautus's Aulularia, Asinaria, Captivi, Rudens, Cistellaria, and Truculentus, and Terence's Phormio and Hecyra. Offering new interpretations of each, he develops a "typology of plot forms" by analyzing structural features and patterns of conventional behavior in the plays, and he relates the results of his literary analysis to contemporary social conditions. He argues that the plays address tensions that were potentially disruptive to the ancient city-state, and that they tended to resolve these tensions in ways that affirmed traditional values. Roman Comedy is an innovative and challenging book that will be welcomed by students of classical literature, ancient social history, the history of the theater, and comedy as a genre